EDUKASI POSISI PERSALINAN BAGI IBU HAMIL DI DESA SALEMBA - Nurul, Nurul Hidayah Bohari; Haerani, Haerani; Nur Fajri, Tri (JCS, 2024)
Childbirth is a physiological process and is an amazing event for a mother and family. Preparation for childbirth is the most important part of the birthing process which aims to improve the mother's health optimally before delivery. In the first stage of labor (cervical opening phase) the family helps prepare the menstrual position. If there is a feeling of wanting to bear and strong contractions occur, help the mother into a half-sitting position or other desired position and make sure the mother feels comfortable. This activity was carried out on December 16 2023, in Salemba Village, Ujung Loe District. There were 8 pregnant women who attended. The methods used start from the preparation stage, implementation stage to evaluation stage. The result of PKM activities is that before education was carried out regarding birth positions, pregnant women only knew 2 birth positions. However, after being given education, pregnant women know the various birthing positions according to the explanation given during the PKM activities